Spatiotemporal assessment of mangrove cover, soil salinity, and nutrient patterns in Chengmai County using remote sensing (2018–2023) - Kashif Ali Solangi; Zexiu Yang; Xiaochun Wei; Farheen Solangi; Di Zeng; Lei Liu; Kangbing Wang; Jinling Zhang; Xiqiang Song (Ecological Indicators, 2025)
The protection, conservation, and restoration of coastal ecosystems, including mangrove forests, are key targets of the United Nations Sustainable Development Goals (SDGs) for 2030. Ground-truth data combined with satellite-based observations provide essential historical insights, enabling the development of dynamic management strategies and the formulation of effective policy interventions. This study assesses the soil characteristics and mangrove cover in Chengmai County by integrating multiple datasets. The results indicate that most of the study area consists of non-saline to low-saline soils, with high and extreme salinity confined to the upper portion of the county. Soil pH remained acidic throughout the region, with values ranging from 4.4 to 6.2. Furthermore, the alkali-hydrolyzed nitrogen content ranged from 109 to 234.9 mg/kg, available phosphorus from 3.5 to 135 mg/kg, and available potassium from 24.3 to 124.1 mg/kg, respectively. Over six years (2018–2023), mangrove cover has shown an increasing trend, with a total expansion of 17.7 %. This increasing trend of mangroves suggests coastal resilience and enhanced ecosystem functionality. However, the observed trend indicates a possible stabilization in mangrove expansion or being influenced by specific environmental and anthropogenic factors regulating mangrove growth in the Chengmai region.